Telemedicine in the management of temporomandibular disorders: A literature review - Chairunnisa, Ricca; Shabrina, Aliyya; Sukotjo, Cortino (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Temporomandibular disorders are clinical disorders involving the muscles of mastication, temporomandibular joints, and related structures. There are several treatments, such as self-help exercises, that can be done at home using remote care, often called telemedicine, after the patient has been directed to do so by a practitioner and evaluated during regular visits. Along with advancement of the times and technology, as well as with the prevention of COVID-19, telemedicine may currently be the main means of self-care for patients at home without losing the supervision of a doctor. Purpose: The purpose of this study is to determine the effect of using telemedicine in the management of temporomandibular disorders. Methods: A systematic literature review was undertaken using literature search methods in electronic databases: PubMed, ProQuest, and Google Scholar. The keywords were "(Telemedicine OR Teledentistry) AND (Temporomandibular disorder) AND (Effect).” The inclusion criteria for selection of the scientific articles were publication from 2012 to 2022, publication in English, and the full paper being available. Results: Seven articles have been included in this review. Based on the results of this systematic study, using telemedicine is considered able to assist the management of temporomandibular disorders by conducting consultation, follow-up, and treatment remotely via telephone, smartphone application, or internet-based or website-based applications. Conclusion: Telemedicine makes it easier for patients who do not have access to a health center to receive consultations and treatments from home, minimizing time and costs.